Correlation of Heat Stress to Hydration Status of Workers at Weaving Section of Tekstile Industries - Danang Adi Prayitno; Siti Rachmawati; Maria Paskanita Widjan; Hashfi Hawali Abdul Matin (Waste Technology, 2020)
Abstract.PT X is a company plastics and textiles that has 3 section of the production process, one of which is the weaving section. During work, workers are exposed to heat stress which can affect hydration status. The objective of the research is to investigate the correlation of heat stress to hydration status of the workers at weaving section PT X. This research used the observational analytical research method with cross sectional approach. Its population was all of morning work with 60 workers at weaving section PT Kusuma Mulia Plasindo Infitex Klaten. Proposive sampling was used to determine its samples. They consisted of 37 workers. The heat stress was measured with Heat Stress Area and hydration status using urine specific gravity laboratory tests conducted by Solo Laboratory. The data were processed and analyzed by using the Spearman test. The result of this research show that the heat stress had a correlation with hydration status as indicated by the p-value = 0,001.